2018
DOI: 10.1111/1742-6723.12950
|View full text |Cite
|
Sign up to set email alerts
|

‘What the hell is water?’ How to use deliberate clinical inertia in common emergency department situations

Abstract: Appropriate deliberate clinical inertia refers to the art of doing nothing as a positive clinical response. It includes shared decision-making to improve patient care with the use of clinical judgement. We discuss common clinical scenarios where the use of deliberate clinical inertia can occur. The insertion of peripheral intravenous cannulae, investigating patients with suspected renal colic and the investigation of low risk chest pain are all opportunities for the thoughtful clinician to 'stand there' and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Clearly, the clinician's awareness of these issues should be raised. The opportunity to practice deliberate clinical inertia (the art of not intervening) has been suggested in the insertion of PIVC …”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the clinician's awareness of these issues should be raised. The opportunity to practice deliberate clinical inertia (the art of not intervening) has been suggested in the insertion of PIVC …”
Section: Introductionmentioning
confidence: 99%
“…and "just to be safe" (78%). [34] Egerton-Warburton et al [35] found that over half of 1029 emergency physicians in the study reduced their implicit "test threshold" well below the explicit threshold set using empirical data on test accuracy and risk of harm from the disease, due to their discomfort with diagnostic uncertainty. [35] Coon et al [16] also highlighted the "shotgun approach" [16] of ordering a broad range of tests and hoping for a positive result somewhere, which is often used in situations of diagnostic uncertainty.…”
Section: Fear Of Malpractice and Litigationmentioning
confidence: 98%
“…[34] Egerton-Warburton et al [35] found that over half of 1029 emergency physicians in the study reduced their implicit "test threshold" well below the explicit threshold set using empirical data on test accuracy and risk of harm from the disease, due to their discomfort with diagnostic uncertainty. [35] Coon et al [16] also highlighted the "shotgun approach" [16] of ordering a broad range of tests and hoping for a positive result somewhere, which is often used in situations of diagnostic uncertainty. However, in assessing factors in uencing tendency to order imaging using hypothetical scenarios, Kini et al's [25] survey of cardiologists and general practitioners did not nd a signi cant association between risk aversion and tendency to order cardiac stress tests and echocardiography (likely due to their small sample size).…”
Section: Fear Of Malpractice and Litigationmentioning
confidence: 98%
“…In the context of emergency department-based interventions, the concept of 'appropriate deliberate clinical inertia' has been framed in recognition of the need to resist inappropriate or unnecessary interventions. 290 It appears that this concept may be appropriated in primary care to recognise situations in people with chronic conditions that do not result, for example, in any change in the dose or nature of medications. Clear agreement between patients and HCPs that emergency admission will not resolve or in any way modify their symptoms or treatment can act as a sound basis for 'shared decision-making to improve patient care with the use of clinical judgement'.…”
Section: Clinical Inertia and Admission As 'The Default Position'mentioning
confidence: 99%
“…Clear agreement between patients and HCPs that emergency admission will not resolve or in any way modify their symptoms or treatment can act as a sound basis for 'shared decision-making to improve patient care with the use of clinical judgement'. 290 Candidacy and 'deservedness'…”
Section: Clinical Inertia and Admission As 'The Default Position'mentioning
confidence: 99%